The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.35434/rcmhnaaa.2021.144.1451
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of self-medication of the population, during the covid-19 pandemic in Peru

Abstract: Background: Describe characteristics of self-medication of the population, in the context of the COVID 19 pandemic. Material and Methods: We carried out a cross-sectional survey with students in a major public Peruvian university. We measured perception of self-medication of the population, as well as characteristics, consequences, and associated factors. Results: A total of 274 students of Pharmacy and biochemistry filled in the questionnaire, 80.3% of which reported to know someone that self-medicated during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Por último, el nivel de escolaridad demostró ser otro factor asociado puesto que en tres estudios se evidenció que el 50% de la población con un nivel correspondiente al bachillerato se automedican. En tanto que los hallazgos de Inostroza-Ruiz et al, encontraron un OR=1,46 asociado al bajo nivel de escolaridad (11,17,19,21).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Por último, el nivel de escolaridad demostró ser otro factor asociado puesto que en tres estudios se evidenció que el 50% de la población con un nivel correspondiente al bachillerato se automedican. En tanto que los hallazgos de Inostroza-Ruiz et al, encontraron un OR=1,46 asociado al bajo nivel de escolaridad (11,17,19,21).…”
Section: Discussionunclassified
“…La automedicación fue variable pues se identificaron estudios con prevalencias entre el 14% y 80% en Perú (3,10,11) Tres estudios realizados en Colombia y Brasil señalan la automedicación con suplementos vitamínicos siendo la vitamina D la más reportada como objeto de automedicación (13,14,16).…”
Section: Prevalencia De Automedicación En América Latinaunclassified
See 1 more Smart Citation
“…A study showed that the prevalence of inappropriate self-medication was 51%, and was associated with the male sex, ages >40 years, and not having health insurance. ( 22 ) As well as this research, other studies have evaluated self-medication with antibiotics and among pregnant women, even during the pandemic; ( 23 26 ) however, self-medication and drug consumption patterns in older adults have not been studied. Considering the demographic transition process in Peru, the proportion of older adults increased from 5.7% in 1950 to 12.7% in 2020, ( 27 ) reinforcing the interest to study this phenomenon in this growing vulnerable population.…”
Section: Introductionmentioning
confidence: 97%